Exploring the regulatory space for improving availability, access and quality of vegetatively propagated crop seed: potato in Kenya - McEwan, M.; Spielman, David J.; Okello, J.J.; Hareau, Guy; Bartle, B.; Mbiri, D.; Atieno, E.; Omondi, Bonaventure Aman Oduor; Assfaw, T.; González, L.; Abdoulaye, Tahirou; Maredia, Mywish K. (International Potato Center, 2021)
Potato ranks second staple food crop in Kenya. The Government seeks rapid yield growth in the potato subsector, however with only 2% of potato seed planted currently certified there is a persistent shortage of quality seed. There is no consensus on an appropriate model for quality seed assurance which can ensure increased availability and access to quality seed by smallholder farmers, while minimizing risk of spread of plant diseases. This study addressed the question of whether the current seed regulatory framework in Kenya and its implementation meets the need for increased availability and access to quality seed potato, for who, and with what consequences? Secondary data and analysis were complemented by semi-structured interviews and focus group discussions involving 72 stakeholders from public, private and civil society conducted in the major potato production areas, and at national level. Our findings show a range of different actors have different and sometimes conflicting interests. Seed potato needs to be produced on a large-scale with enough land and resources to meet rotation and isolation standards and inspection costs. However, this has implications for equitable participation in the seed potato industry. Current regulatory and inspection procedures are perceived by small-scale seed producers as policing rather than facilitating quality seed production. This highlights compromises between achieving short term food security and managing risk of spread of plant diseases. The feasibility of different approaches to manage bacterial wilt and potato cyst nematode are discussed with implications for different scales of seed production. Several options are reviewed, with their trade-offs, emphasising the need to for inclusive stakeholder consultations to negotiate towards a common interest space.